Pengaruh Agresivitas Pajak, Leverage, dan Umur Perusahaan terhadap Pengungkapan Corporate Social Responsibility (CSR) - Hanna, Laurencia Audrey; Prihatni, Rida; Purwohedi, Unggul (LPPM Universitas Negeri Jakarta, 2023)
The purpose of this research is to examine and analyze the effect of tax aggressiveness on corporate social responsibility disclosure, the effect of leverage on corporate social responsibility disclosure, and the effect of firm age on corporate social responsibility disclosure. The sampling technique used in this study was purposive sampling. Researchers used secondary data, namely from annual reports and sustainability reports of mining companies listed on the Indonesia Stock Exchange from 2020 to 2022. The data analysis technique in this study used panel data regression through data processing carried out in Eviews 12 software. The results obtained in this study are as follows: (a) Tax aggressiveness has no significant effect on corporate social responsibility disclosure; (b) Leverage has no significant effect on corporate social responsibility disclosure; and (c) Company age has a positive and significant effect on corporate social responsibility disclosure.